Four desert fathers Pambo, Evagrius, Macarius of Egypt, and Macarius of Alexandria ; Coptic texts relating to the Lausiac history of Palladius - Vivian, Tim 1951-; Greer, Rowan A. 1934-2014 (Crestwood, N.Y. St Vladimir's Seminary Press, 2004)
The life of Pambo -- The life of Evagrius -- The life of Macarius the Great -- The life of Macarius of Alexandria -- Seven goals of anti-origenism -- Syriac lausiac history -- Evagrius debates three demons (Cotelier) -- Apa Aphou and Archbishop Theophilus -- Debate the image of God.
The life of Pambo -- The life of Evagrius -- The life of Macarius the Great -- The life of Macarius of Alexandria -- Seven goals of anti-origenism -- Syriac lausiac history -- Evagrius debates three demons (Cotelier) -- Apa Aphou and Archbishop Theophilus -- Debate the image of God
Includes bibliographical references (p. 195-202) and indexes
Archivierung prüfen
Keywords: Desert Fathers -- Biography; Christian biography -- Egypt; Spiritual Life -- Christianity; Desert Fathers -- Quotations